Respuesta :

Answer:

f⁻¹(x) = x+2 / 3

Step-by-step explanation:

Given function is:

f(x) = 3x-2

We have to find the inverse of the given function.

Put y = f(x)  in given function, we have

y =3x-2

Adding 2 to both sides of the above equation we have

y+2 = 3x-2+2

y+2 = 3x

Dividing by 3 to both sides of the above equation, we have

y+2 / 3 = 3x / 3

y+2 / 3 = x

Put x = f⁻¹(y) in the above equation we have

y+2 / 3 = f⁻¹(y)

Swapping equation we have

f⁻¹(y) = y+2 / 3

Replace y with x we have

f⁻¹(x) = x+2 / 3   which is the answer.

ACCESS MORE